The Developments Of Proportional-Double Derivative-Linear Quadratic Regulator Controller For Attitude And Altitude Motions Of A Quadcopter - Raihan, Mohamad Norherman Shauqie Mohamed (Universiti Sains Malaysia, 2019)
Unmanned Aerial Vehicle (UAV), in this case, a quadcopter, is a small-scale UAV that has been widely used in the recent years due to its capability to perform a various application either in the military or civilian application such as environment monitoring, surveillance, and inspection. In order to guarantee a high performance of the quadcopter in the various mission applications, it needs reliable hardware and control systems. Therefore, it is important to developing an effective control algorithm for the controller for the performance and application of the quadcopter. In this thesis, studies of the attitude control and stabilization of the quadcopter through a simulation in Matlab/Simulink software has been done. First, several controllers, Proportional-Integral-Derivative (PID), Proportional-Derivative (PD), Linear Quadratic Regulator (LQR), Proportional-Linear Quadratic Regulator (P-LQR), and Proportional-Derivative-Linear Quadratic Regulator (PD-LQR) controller have been chosen to be studied and analyzed. After that, from the analysis obtained another controller was proposed to improve the performance of the quadcopter control. It is found that by adding another Derivative gain in the PD-LQR control system, the performance can be improved further. Thus, a Proportional-Double Derivative-Linear Quadratic Regulator (PD2-LQR) controller has been designed and developed. The mathematical model of the quadcopter using the Newton-Euler approach is applied to the controller system illuminate the attitude and altitude motions of the quadcopter. The simulation results of the proposed PD2-LQR controller have been compared with the PD, PID, LQR, P-LQR, PD-LQR controller. The comparative study of the response plots reveals that the proposed PD2-LQR controller significantly improves the performance of the control system in almost all responses. In pitch motion, the PD2-LQR controller can improve the rise time up to 82.9% in average compared to other controllers, settling time improved by 86.58% in average, overshoot improved by 39.16% in average, steady-state error improved by 39.2% in average, and RMSE improved by 28.32% in average. In roll motion, rise time improved by 63% in average, settling time improved by 65.5% in average, overshoot improved by 57.7% in average, steady-state error improved by 32.82% in average, and RMSE improved by 29.4% in average. In yaw motion, rise time improved by 41.8% in average, settling time improved by 41.5% in average, overshoot improved by 34.3% in average, the improvement of steady-state error in yaw motion is very small it can be approximately equal to zero, and RMSE improved by 19.4% in average. In altitude motion, rise time improved by 31.7% in average, settling time improved by 52.7% in average, overshoot improved by 75.7% in average, and RMSE improved by 10.2% in average. Therefore, the proposed PD2-LQR controller is best-suited for the modelled quadcopter in all four motions, pitch, roll, yaw, and altitude.